NILAI PENDIDIKAN KARAKTER DALAM NOVEL SEPERTI DENDAM RINDU HARUS DIBAYAR TUNTAS KARYA EKA KURNIAWAN - Mila Tri Ramadani; Iswadi Bahadur; Samsiarni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted to describe and analyze the character education values contained in the novel " Seperti Dendam Rindu Harus Dibayar Tuntas" by Eka Kurniawan. These character education values consist of virtue, beauty, work, patriotism, democracy, unity, morality, humanity, justice, and cooperation.The research method used was qualitative. The method used was descriptive analysis. The data in this study consisted of words, sentences, and discourse. The data source was the novel " Seperti Dendam Rindu Harus Dibayar Tuntas" by Eka Kurniawan. The researcher chose this novel as a data source because it tells the story of a character named Ajo Kawir, who becomes impotent due to an incident he witnessed as a child. The instrument used in this research was a data inventory format. The data collection technique used in this study was a literature review. The data validation technique used investigator triangulation. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results of this study indicate that character education values are represented through events, characters, and meaningful dialogue. These values include virtue, beauty, work, patriotism, democracy, unity, morality, humanity, justice, and cooperation.